KONTRIBUSI STATUS GIZI TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PENJASORKES) DI MADRASAH TSANAWIYAH (MTS) NEGERI DURIAN TARUNG - Edwarsyah, Edwarsyah (STKIP Pasundan, 2015)
This study aims to look at the contribution of nutritional status to the learning outcomes of physical and health physical education (Penjasorkes) for students in Madrasah Tsanawiyah (MTs) Negeri Durian Tarung. The research method used to uncover this problem is the correlational method. The sample of this study were all students of class VII (seven) Madrasah Tsanawiyah (MTs) Negeri Durian Tarung, totaling 36 people. Nutritional status instruments were obtained using weight scales and microtoa, and learning outcome data were obtained from report cards in semester 1 of the 2012/2013 academic year. Analysis techniques used product moment correlation and contribution formulas (r² x 100%) with a significance level of ? 0.05 . Based on the results of calculation of the contribution obtained by the relationship between nutritional status of student learning outcomes of students at Madrasah Tsanawiyah (MTs) Negeri Durian Tarung by 20.34%. In conclusion, there is a significant contribution given by the nutritional status of the Penjasorkes learning outcomes for students of the Madrasah Tsanawiyah Negeri Durian Tarung that is equal to 20.34%. While the rest can be influenced by other factors.